SPSS statistics - Salcedo, Jesus; McCormick, Keith (Hoboken, NJ : John Wiley & Sons, Inc., 2020)
If you're involved in research, marketing, data mining, or academics, you probably know how useful SPSS (Statistical Package for the Social Sciences) can be. Here's the guidebook that will get you up to speed on SPSS 27 before you know it. A wealth of upgrades makes SPSS 27 even more valuable, and these authors, who share 55 years of experience working with and teaching SPSS, walk you through every one. You'll master the revised interface, discover some new functions, build graphs, explore advanced data analysis tools, and much more.
Part 1: Getting started with SPSS -- Part 2: Getting data into and out of SPSS -- Part 3: Messing with data in SPSS -- Part 4: Graphing data -- Part 5: Analyzing data -- Part 6: Getting more advanced with analyzing data -- Part 7: Making SPSS your own -- Part 8: Programming SPSS with command syntax -- Part 9: The part of tens.
Includes index.
Keywords: SOCIAL SCIENCES -- RESEARCH STATISTICAL METHODS